واقع استخدام استمارة الاستبانة في البحوث الاجتماعية: دارسة تحليلية لدارسات ميدانية - مسعود العقيبي انتصار (مجلة كلية الاداب, 2024)
This research is located in a space located between reality and what is hoped for, between a reality in which many research tools are used to achieve real and reliable collection of scientific data, and among those tools is the questionnaire form, its requirements and implementation mechanisms known to researchers. Based on this reality, the idea that I present in this study is oriented toward what is hoped, and confirms that there are other tools that we can use to survey broader scopes and horizons than (questionnaires), and obtain from them more in-depth data and more accurate results of description and analysis, such as: (in-depth interviews). ) and (case studies) and (CVs) and (life biographies). Accordingly, this study will fall under the framework of the second axis of the conference, which examines the reality of scientific research in Libya, by presenting the reality of the questionnaire form in social studies; By analyzing three social studies conducted on Libyan society, examining the repercussions of the Internet on some social issues, with samples from the cities of Benghazi and Ajdabiya; In an attempt to re-analyze its results; And monitoring the most important repercussions that the Internet has on some aspects of social life, which are: (social values - social relations - educational attainment). The analyzes revealed that there is diversity and difference in the three previous studies, in terms of method, samples, objectives, hypothesis, it examines the extent to which there is a negative impact of the Internet on social life, but all The hypotheses in the three previous studies were rejected, and therefore this study aims to answer some methodological questions related to the questionnaire, in an attempt to raise the importance of research tools that collect data from depth more than from the surface.and hypotheses, and that they all share one data collection tool, which is the questionnaire form. Despite starting from a basic